2016
DOI: 10.1016/j.physletb.2016.08.047
|View full text |Cite
|
Sign up to set email alerts
|

The weak mixing angle from low energy neutrino measurements: A global update

Abstract: Taking into account recent theoretical and experimental inputs on reactor fluxes we reconsider the determination of the weak mixing angle from low energy experiments. We perform a global analysis to all available neutrino-electron scattering data from reactor antineutrino experiments, obtaining sin 2 θW = 0.252 ± 0.030. We discuss the impact of the new theoretical prediction for the neutrino spectrum, the new measurement of the reactor antineutrino spectrum by the Daya Bay collaboration, as well as the effect … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 42 publications
2
30
2
Order By: Relevance
“…As our first application, we turn off the NSIs and fit sin 2 (θ W ) to the Borexino low-energy data in Sec. 4 and compare to the results of several other studies [18][19][20].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…As our first application, we turn off the NSIs and fit sin 2 (θ W ) to the Borexino low-energy data in Sec. 4 and compare to the results of several other studies [18][19][20].…”
Section: Introductionmentioning
confidence: 58%
“…There is ongoing interest in the low-energy determination of the weak-mixing angle sin 2 (θ W ) [20,51]. Presently the lowest energy determination of the weak-mixing parameter sin 2 (θ W ) is that provided by the parity-violation measurement in 133 Cs at 2.4 MeV [52][53][54].…”
Section: The Standard Model: Low-energy Fit To Sin 2 (θ W )mentioning
confidence: 99%
“…A degenerate area is found that cannot be excluded by the current data, due to the cancellations involved in Eq. (21). For heavy mediator masses, M Z √ 2M T N ∼ 50 MeV, this degeneracy remains unbroken and depends on the ratio…”
Section: Vector Z and Scalar φ Mediatorsmentioning
confidence: 99%
“…The PVDIS Collaboration [7] at the 6 GeV CEBAF complex at JLab scattered polarized electrons deep-inelastically from deuterium, and the SoLID Collaboration [8] will increase the PVDIS precision in the future by benefiting from the energy upgraded CEBAF and a correspondingly higher and broader Q 2 range. Other approaches include neutrino and anti-neutrino deep inelastic scattering [9],ν-e scattering near nuclear reactors [10], and parity violation in atoms [11] and ions [12]. For more details, see the recent reviews on low energy measurements of the weak mixing angle [13], on the weak neutral current [14], and on weak polarized electron scattering [15].…”
Section: Introductionmentioning
confidence: 99%